Organic dye removal by MnO2 and Ag micromotors under various ambient conditions: The comparison between two abatement mechanisms. (October 2017) - He, Xu; Bahk, Yeon Kyoung; Wang, Jing
Abstract: MnO2 - and Ag- based micromotors were developed recently as new types of micromotors with the advantage of low costs and have been utilized to treat environmental pollutants. However, knowledge about the effects of ambient conditions on the performance of them is still lacking. In this article, the influences of pH, electrolytes and surfactant on the treatment of organic dye (with methylene blue as the representative) by the commercial MnO2 and Ag micromotors with H2 O2 as the fuel were studied. In the motion visualization experiments, besides the routine types of trajectories, the circular motion of micromotors around the already formed bubbles was observed for the first time. In the pollutant removal experiments, two abatement mechanisms (catalytic degradation and adsorptive bubble separation) were studied. The decolorization efficiency for MnO2 due to catalytic degradation increased with the increasing pH, which disagreed with previous studies in which no H2 O2 was added. The inhibitory effects of the tested electrolytes were in the order: CaCl2 >NaNO3 >NaCl. Surfactant can increase the decolorization efficiency only under highly alkaline conditions. For Ag, decolorization only occurs with the existence of surfactant at high pH values (pH = 11.4) indicating that the dominant mechanism is adsorptive bubble separation. Graphical abstract: Highlights: The higher pH, the higher treatment efficiency of pollutant by MnO2 micromotors. The inhibitory effects of the electrolytes were in the order: CaCl2  > NaNO3  > NaCl. Only under high pH, surfactant can increase the overall treatment efficiency. Ag micromotors can remove the pollutants by physical adsorption under high pH.